The fruit set of pears with special reference to cv. 'Doyenne du Comice' (Pyrus communis L.) - Du Plessis, Petru (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1996.